The Evolution Of Research On Academic Cheating Behavior Based On The Theory Of Planned Behavior (TPB): Perspectives For Future Research - Respati, Yudit Ayu; Harsono, Mugi (STIE AUB Surakarta, 2023)
This study aims to present a summary of various studies that explore academic cheating behavior with the support of a theory or conceptual framework so that it can be used as a valuable reference for monitoring the development of research on academic cheating behavior driven by the Theory of Planned Behavior (TPB). It is also hoped that this article can become a basis for inspiration for further research development in this domain in the future. The method applied in this study is a literature review using the connectedpapers.com platform. A search for relevant articles was conducted using the keywords